Keputusan Rasional Amerika Serikat Dalam Pembangunan Pipa Minyak Keystone XL oleh Transcanada Tahun 2008-2015 - Macitra, Ni Putu Wilma; Kumala Dewi, Putu Ratih; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT The United States and Canada have established bilateral cooperation since 1988 in CUSFTA. This research will use a rational actor model by Alex Mintz. The author's hypothesis is the United States rejects the construction of the Keystone XL oil pipeline because the Keystone XL pipeline will negatively affect the economy, environment and politics of the United States. This decision was taken in connection with the decision of the United States during the Obama administration to concentrate on the environment, therefore a state that is rational actor would reject the construction of the Keystone XL pipeline which would bring domestic opposition to the population of the United States. This research then tries to analyze domestic politics that influence policy making and policy making processes on the basis of profit and loss.   Keywords : Keystone XL oil pipeline, rational actor, domestic factor in foreign policy, Environment.